The genetic architecture of depression in individuals of East Asian ancestry: a genome-wide association study - Giannakopoulou, O; Lin, K; Meng, X; Millwood, I; Chen, Y; Chen, Z; Walters, RG (American Medical Association, 2021)
Importance Most previous genome-wide association studies (GWAS) of depression have used data from individuals of European descent. This limits the understanding of the underlying biology of depression and raises questions about the transferability of findings between populations.